Virtual hospital a digital library of health information. - University of Iowa. (Iowa City, Iowa University of Iowa, 1992)
Offers textbooks and booklets for health care providers and patients and delivers continuing education to health care providers' offices and homes.
Virtual hospital home--Virtual children's hospital home--Site map--Mirror sites -- Search--Provider health topics A-Z--Provider textbooks -- Patient health topics A-Z--Patient textbooks -- About us--Continuing education--Translations--Links--Support us.
Title from home page (viewed June 8, 2004).
Text, mages, and atlases.
Mode of access: World Wide Web.
Keywords: Health -- Computer network resources; Medicine -- Computer network resources